2018
DOI: 10.1007/s11482-018-9645-9
|View full text |Cite
|
Sign up to set email alerts
|

General Education Learning Outcomes and Demographic Correlates in University Students in Hong Kong

Abstract: Although there are studies showing that higher education would benefit university students, empirical research that comprehensively assesses student general education learning outcomes and related demographic correlates based on longitudinal data is minimal, especially in the Chinese context. To address the research gaps, the present study was conducted to investigate learning outcomes amongst university students in one university in Hong Kong based on a four-year longitudinal design (N = 460). Four dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(48 reference statements)
0
4
1
Order By: Relevance
“…However, as the course was offered in 7 weeks during the summer term, the chance for students to naturally have significant improvements in leadership qualities and well-being in such a short time period was not high. In particular, previous studies concluded that university students did not necessarily make gains in their leadership competence and well-being merely because of maturation during the university period (Roohr et al, 2017;Yu et al, 2019). Therefore, the positive changes in service leadership qualities and well-being among students revealed in the present study are unlikely to be entirely attributed to maturation.…”
Section: Discussioncontrasting
confidence: 56%
“…However, as the course was offered in 7 weeks during the summer term, the chance for students to naturally have significant improvements in leadership qualities and well-being in such a short time period was not high. In particular, previous studies concluded that university students did not necessarily make gains in their leadership competence and well-being merely because of maturation during the university period (Roohr et al, 2017;Yu et al, 2019). Therefore, the positive changes in service leadership qualities and well-being among students revealed in the present study are unlikely to be entirely attributed to maturation.…”
Section: Discussioncontrasting
confidence: 56%
“…This process needs to proceed without interruption in China [ 5 ]. SLO assessment in the Chinese context furthermore needs comprehensive measures in order to equip the students with better learning outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process needs to proceed without interruption in China [5]. SLO assessment in the Chinese context furthermore needs comprehensive measures in order to equip the students with better learning outcomes [12]. Zhoc, Chung [5], argued that SLOs (social, cognitive, self-growth outcomes and satisfaction with university experience) are at the core of the educational goals of Chinese HEIs that deliver benefits even after the end of school life.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a lot of freshmen who are doing their GE at the Hong Kong Polytechnic University at their first year of university study feel pressured and struggled when it comes to the independent and active learning approach. This can be mainly attribute to the reason that a lot of these traditional and pragmatic students were used to didactic teaching and rote memorisation before entering university (Yu et al, 2019). Meanwhile, some academics at the University of Hong Kong strongly insist the maintenance of their disciplinary territories when the Common Core Curriculum at its GE is introduced as they think such type of interdisciplinary education is hampering the pursuit of disciplinary foundation and specialisation (Tsui, 2012).…”
Section: Issues Of the Policy Borrowing Of General Education In Hong ...mentioning
confidence: 99%